COMPARATIVE IMPACT OF FORMULATED HERBAL NUTRACEUTICALS ON PERFORMANCE OF CROSSBRED CALVES - NIWAS, RAM; D. P. SINGH,; V. K. PASWAN,; M. ALBIAL , ABED; S. KUMAR, (The Bioscan, 2013)
Present study was designed with the aim to see the influence of formulated and marketed herbal (Herbstone) nutraceuticals on growth performance, dry matter intake (DMI) and digestibility coefficient of crossbred calves. For this purpose twenty seven crossbred calves weighing about 58 to 65 kg were selected and divided randomly into three similar groups (3 animals in each) for three different trials (Rainy, Winter and Summer season) and each trial was conducted for a period of 60 days excluding pre experimental period. To meet out the nutritional requirement as per NRC (1989) recommendation; all the calves were fed on seasonally available chopped roughages and concentrate mixture. Group T2 and T3 were supplemented with 2.0% of concentrate ration with formulated and marketed nutraceuticals respectively while group T1 (control) was fed without any nutraceuticals. During each trial body length, height, weight, girth circumferences, DMI and digestibility coefficient were measured at 0, 30 and 60 days of interval. As a result of the administration of the two different nutraceuticals given to calves; had showed significantly (P<0.05) higher body weight gain, length, girth circumferences, DMI and digestibility coefficient than control group but body height had not shown any significant difference amongst treatments and periods. DM digestibility was significantly lower (p<0.05) in control group.